Registration of Transfer of Joint Ownership of Land Rights After Divorce - I Nyoman Alit Puspadma (Fakultas Hukum, Universitas Warmadewa, 2023)
The maintenance of land registration data has been regulated in statutory regulations, among others regulating the transfer of land rights that occur by law in the form of inheritance. Of all the HAT transfer registrations, there is no regulation regarding the registration of the land rights transfer jointly owned by the divorced husband and wife. A husband and wife bought a plot of land and registered it in the husband's name, then they divorced and agreed that the land would become part of the wife. The question arises what are the effects of divorce on assets and how is the procedure for registering the transfer ofland rights between husband and wife who are divorced from land rights belonging to them together? Thus, this study aims to discuss the effects of divorce on assets and to find out how to register the transfer of land rights between husband and wife who are divorced. This type of normative legal research, with primary, secondary and tertiary legal materials, uses statutory and case approaches. Legal material is analyzed by legal analogy construction with deductive thinking method. The results obtained show that first the wife's name is recorded in the certificate, then an APHB is made by the Land Deed Officials and registered at the Land Office so that the certificate is written in the name of the wife.